Prevalence of gastric cancer following colorectal endoscopic submucosal dissection for lesions more than 20 mm: A retrospective analysis - Yuri Tomita; Naohisa Yoshida; Hideki Ishikawa; Takahiro Otani; Reo Kobayashi; Hikaru Hashimoto; Ryohei Hirose; Osamu Dohi; Ken Inoue; Yukiko Morinaga; Yoshito Itoh (DEN Open)
Abstract Objectives Colorectal endoscopic submucosal dissection (ESD) for large tumors is spreading worldwide. Gastric cancer (GC) sometimes occurs after colorectal ESD. However, its status including frequency and risk factors have not been examined well. In this study, we analyzed the detailed status of GC after colorectal ESD. Methods This was a single‐center retrospective study. Patients receiving colorectal ESD between 2010 and 2018 were reviewed. All patients were recommended to receive esophagogastroduodenoscopy (EGD) for screening. Finally, 436 patients receiving EGD, who underwent colorectal ESD for lesions of ≥20 mm were analyzed. The primary outcome was the GC rate after colorectal ESD, including intramucosal cancer. As a control, we compared it to the GC rate in matched Japanese national cancer registry data. The secondary outcome was risk factors for developing GC. Results The mean age was 66.9 ± 10.6 and 55.3% were males. The GC rate was 5.96% (26/436) with a median observation period of 27 months. It was significantly higher than the mean GC rate in the diagnosed age calculated with the cancer registry (0.26%, observed value/expected value ratio [95% confidence interval]: 22.20 [14.50–32.53], p < 0.01). The comparison between cases with and without GC showed that significant risk factors were male (p = 0.02) and smokers (p < 0.01) and their GC rates were 8.3% and 10.9%. Also, in the limited cases, Helicobacter pylori infection (past and present) and atrophic gastritis were significant and their GC rates were 11.1% and 11.6%. Conclusion The GC rate was high after resecting colorectal tumors of ≥20 mm, suggesting the necessity of EGD.